PENGARUH SALEP DAUN BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS) TERHADAP PENYEMBUHAN LUKA AKUT MENCIT (MUS MUSCULUS) - Mira Rianty (Coping: Community of Publishing in Nursing, 2014)
Normal acute wounds will heal through the phases of wound healing. The main  goal  in  wound  treatment  is  to  heal  the  wound  in  the  shortest  time.  Binahong  leaves (Anredera cordifolia (Ten.) Steenis) has been used by the Indonesian as a traditional medicine to heal wounds. The purpose of this study was to determine the effect of Binahong leaves ointment  (Anredera  cordifolia  (Ten.)  Steenis)  against  acute  wounds  healing  of  mice  (Mus musculus) This research is a form of True Experiment with the Post-test Only Control Group Design.  The  sample  consisted  of  32  mice  (Mus  musculus)  that  were  selected  by  simple random  sampling  technique,  which  is  divided  into  two  groups,  the  control  group  and  the treatment  group.  The  treatment  group  was  given  Binahong  leaves  ointment  (Anredera cordifolia  (Ten.)  Steenis)  wound  care,  meanwhile  the  control  group  was  given  povidone iodine ointment wounds care. Wound length was measured using calipers. The seventh day wound length  used for analyzing data. The  results obtained by the average of 0.1069 seventh day  length  wound  in  the  treatment  group  and  in  the  control  group  were  0.4325.  Based  on Independent-Samples  T  Test,  the  difference  was  statistically  significant,  with  a  t  value  of 7.295 and p-value of 0.000, which means there was an influence of Binahong leaves ointment (Anredera cordifolia (Ten.) Steenis) against acute wound healing of mice (Mus musculus)